2018
DOI: 10.1111/hsc.12563
|View full text |Cite
|
Sign up to set email alerts
|

Between older adults' needs and the law: The Israeli Long Term Care Insurance Law from the Perspectives of Service Users and Providers

Abstract: The Israeli Long Term Care Insurance Law (LTCIL) was one of the first long term care insurances in the world to support older adults and their family members and allow them to stay in their homes for as long as possible. The present study aimed to evaluate the perspectives of older adults, their family members and home care workers regarding the LTCIL. Views of workers of the National Insurance Institute (NII), which is directly responsible for the enactment of the law, are also integrated. Interviews were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Given the prominent place the topic of perceived discrimination and stigma received during interviews, perceived discrimination and stigma became the focus of this study. Other themes that emerged during the coding process were delineated in papers on intergenerational solidarity in the Arab community [40] and perceptions of the NII in light of the Long-Term Care Insurance Law [41]. The focus of each paper on a specific core category was done using selective coding, which involves the identification of a core category and related themes which correspond with it [42].…”
Section: Introductionmentioning
confidence: 99%
“…Given the prominent place the topic of perceived discrimination and stigma received during interviews, perceived discrimination and stigma became the focus of this study. Other themes that emerged during the coding process were delineated in papers on intergenerational solidarity in the Arab community [40] and perceptions of the NII in light of the Long-Term Care Insurance Law [41]. The focus of each paper on a specific core category was done using selective coding, which involves the identification of a core category and related themes which correspond with it [42].…”
Section: Introductionmentioning
confidence: 99%
“…The bodies of elderly individuals who have experienced ageist discrimination may interpret these negative experiences as social stressors, and such experiences can directly affect health through hypothalamic‐hypophysis‐adrenal activation, and this, in turn, can lead to the secretion of cortisol and an increase in systemic inflammation 91 . Perceived ageism has well‐known and negative impacts on mental health 92,93 . Ageism makes people feel alone, 94 leads to symptoms of depression, 95 and may be an element of stress for which individuals are unable to develop effective coping mechanisms 96 .…”
Section: Discussionmentioning
confidence: 99%
“…91 Perceived ageism has well-known and negative impacts on mental health. 92,93 Ageism makes people feel alone, 94 leads to symptoms of depression, 95 and may be an element of stress for which individuals are unable to develop effective coping mechanisms. 96 Shin et al 48 48 It also reported that healthcare workers prefer to work with younger generations.…”
Section: Discussionmentioning
confidence: 99%
“…La segunda etapa tiene lugar con el surgimiento de la geriatría, como especialidad médica destinada al estudio del envejecimiento humano, y se consolidó con la aparición de la gerontología, con el estado del bienestar desde 1970 a nuestros días (Greve, 2020: 109;Ayalon, 2018;Le Bihan y Martín, 2010;Schmid, 2005). Durante esta instancia, se profundizó la aplicación del enfoque sanitario sobre estos servicios, el cual aún convive con las actuales exigencias derivadas del enfoque sociojurídico integral (Dabove, 2012: 10;Fernandez Oliva, 2014: 53;Pérez Bonet, 2010: 178).…”
Section: Servicios De Cuidados De Largo Plazo: Conceptos Y Antecedentesunclassified